2000
DOI: 10.2190/lulr-bad9-yeet-pd0m
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Family Planning among Currently Married Women in Jordan Badia

Abstract: This article reports the results of the first household survey ever conducted in Jordan Badia to include questions on knowledge, attitude, and practices (KAP) among 15–49 currently married women in Jordan Badia toward family planning. The Jordan Badia is the eastern part of Jordan populated by Bedouins who make up about 7 to 9 percent of the 4.8 million total population of Jordan. Using convenience sampling procedure, a total of 450 respondents, 50 from each of nine villages, were selected for participation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…13,21,12 Non-users in this study were 42% similar to 55%, 44.6% and 47% in study by Srinivasan et al, Prachi et al and Rozina et al respectively 10,14,13 Lack of knowledge is the main reason for not using contraception as in various Indian studies but opposite to in various other studies where partners opposition was the main reason for not using contraception. 12,13,19,24,25 Approval of family planning was shown by 56% of males, as perceived by their wives same as 53.6% in study by Lavanya et al and other studies of Sindh and Punjab, where 78% and 74% of husbands approved the use of contraceptive methods at the time of survey. 12,21 In the present study, 44% of respondent's husband disapproved family planning, similar to 46.45% and 54% of results by Lavanya et al and Etuk et al 12,20 A opposite pattern was also found in Eastern Turkey, where husband's disapproval was the main factor for not using any family planning method among married women.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…13,21,12 Non-users in this study were 42% similar to 55%, 44.6% and 47% in study by Srinivasan et al, Prachi et al and Rozina et al respectively 10,14,13 Lack of knowledge is the main reason for not using contraception as in various Indian studies but opposite to in various other studies where partners opposition was the main reason for not using contraception. 12,13,19,24,25 Approval of family planning was shown by 56% of males, as perceived by their wives same as 53.6% in study by Lavanya et al and other studies of Sindh and Punjab, where 78% and 74% of husbands approved the use of contraceptive methods at the time of survey. 12,21 In the present study, 44% of respondent's husband disapproved family planning, similar to 46.45% and 54% of results by Lavanya et al and Etuk et al 12,20 A opposite pattern was also found in Eastern Turkey, where husband's disapproval was the main factor for not using any family planning method among married women.…”
Section: Resultsmentioning
confidence: 81%
“…25 However, husband support for family planning was significantly higher in a Jordanian study. 19 Attitude of husband was found to be an important predictor for contraception use. In rural areas, husband being the dominant member plays the pivotal role in approving the family size and contraceptive practices.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Analysis also controlled for rural versus urban residence and Badia versus non-Badia residence. The Badia is a rural area in north-eastern Jordan that is home to the Bedouins; the Bedouins tend to be more socially conservative than other Jordanians and contraception use is less prevalent among women in this area [19]. Whether or not the respondent had menstruated within the past 3 months was used as a proxy for pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 In the present study, 36.8% of males disapproved family planning,which is lower than the findings (59%) of Mustafa et al 33 . However, husband support for family planning was significantly higher in a Jordanian study 34 . Attitude of husband was found to be an important predictor for contraception use.…”
Section: Discussionmentioning
confidence: 77%